On the assessment of a VOF based compressive interface capturing scheme for the analysis of bubble impact on and bounce from a flat horizontal surface - ROBINSON, ANTHONY; ALBADAWI, ABDULALEEM; MURRAY, DARINA (My University, 2014)
The process of free rise, collision on and bounce from a solid horizontal surface for a single isolated bubble is investigated by numerical simulations based on the Volume of Fluid method (VOF). The volume fraction advection equation is solved algebraically using the compressive scheme implemented in the CFD open source library (OpenFOAMR ) using both axi-symmetrical and three dimensional domains. The solution sensitivity to the mesh refinement towards the solid boundary and the contact angle formulation (static and dynamic) are assessed with two different fluid mixtures for a range of Bond numbers [0.298 − 1.48] and two different surface hydrophilicities. Numerical results are assessed against published as well as new experiments to include both axi-symmetrical and three dimensional rise trajectories. The investigation addresses the liquid microfilm formation and drainage considering both flow and pressure fields and bubble dynamic characteristics over successive rebounds. Results highlight the importance of resolving the liquid micro layer at the interface between the gas and solid surface in particular in the case of superhydrophobic surfaces. A coarse mesh is shown to precipitate the liquid film drainage. This results in early formation of a triple phase contact line (TPCL) which can occur as soon as the first rebound whereas physical observations indicate that this typically happens much later at a stage whena significant part of the bubble kinetic energy has been dissipated following several rebounds. As a result numerical predictions are shown to be much more sensitive to the contact angle formulation than when a refined mesh allows a more accurate representation of the film drainage. In this case, static and dynamic contact angle models give broadly similar rebound characteristics. Following validation, the numerical simulations are used to provide some useful insight in the mechanisms driving the film drainage and the gas liquid interface as it interacts with the solid surface
PUBLISHED
Keywords: Gas-Liquid Flow; VOF method, Bubble bouncing; static and dynamic contact angle; mesh resolution; film drainage; Gas-Liquid Flow; VOF method, Bubble bouncing; static and dynamic contact angle; mesh resolution; film drainage